Induced Seismic Events - Knoll, Peter; Kowalle, Georg (Pageoph Topical Volumes, 1996)
Induced seismic events are of high scientific and economic significance. They are the result of human activities interacting with regional and local tectonics, changing the local crustal stress state by mining, extraction of rock masses, injection of fluids into the rock massif, and by changing the surface loading and pore pressure state near large reservoirs. Within Europe the study of induced seismic events has a long tradition and international scientific organizations have actively stimulated the co-operation in this field. During its General Assembly in September 1994, the European Seismological Society organized the symposium "Induced Seismic Events". The focus of this symposium was concentrated on induced events in central and eastern Europe, as well as in the former Soviet Union. The major contributions to the symposium, and also some Chinese, Canadian, and South African results are presented here. Case studies as well as data analyses and methodological studies are included. Seismologists and specialists working in the field of geohazard prevention will find much information in this volume that is pertinent to their work